2016
DOI: 10.4300/jgme-d-15-00792.1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Outpatient Teledermatology Education Into the Dermatology Resident Curriculum

Abstract: T elemedicine has the potential to transform how we deliver tomorrow's health care, and residents must learn how to practice on this platform. There is a shortage of dermatologists in the United States, particularly in rural areas, where 1 in 8 primary care visits is related to skin disease.1 Some of the benefits of teledermatology (TD) are the potential to increase access, reduce wait times, and provide costeffective care. In the outpatient setting, literature has consistently demonstrated a comparable accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…11 Given the potential for improved access to care, 9,28,29 high patient satisfaction, 18,19 and cost savings, 11,30 the use of teledermatology is expected to increase. 11,13,17,31 In this study, we demonstrated that an innovative online model for healthcare delivery can foster increased access to high-quality specialty care for psoriasis patients. We showed that patients, PCPs, and dermatologists were highly satisfied with online care.…”
Section: Discussionmentioning
confidence: 78%
“…11 Given the potential for improved access to care, 9,28,29 high patient satisfaction, 18,19 and cost savings, 11,30 the use of teledermatology is expected to increase. 11,13,17,31 In this study, we demonstrated that an innovative online model for healthcare delivery can foster increased access to high-quality specialty care for psoriasis patients. We showed that patients, PCPs, and dermatologists were highly satisfied with online care.…”
Section: Discussionmentioning
confidence: 78%
“…[ 20 21 ] Various centers have already added these modes of learning as residents are evaluated using this tool. [ 22 23 ] It also connects dermatologists from very different ethnicities and cultures to exchange knowledge with each other. [ 24 ] In India, while virtual teaching was not much practiced till now, this pandemic has opened doors to various webinars and virtual rounds.…”
Section: Discussionmentioning
confidence: 99%
“…Several dermatology residency curricula have already integrated teledermatology to improve residents' diagnostic acumen of skin diseases through cased‐based practice and supervision from trained dermatologists. Integration of this technology into dermatology resident curricula may also fulfill certain competencies, such as medical knowledge and practice‐based learning, in the Dermatology Milestone Project by the Accreditation Council for Graduate Medical Education (ACGME) …”
Section: Introductionmentioning
confidence: 99%
“…Integration of this technology into dermatology resident curricula may also fulfill certain competencies, such as medical knowledge and practice-based learning, in the Dermatology Milestone Project by the Accreditation Council for Graduate Medical Education (ACGME). [6][7][8] International Journal of Dermatology 2018, 57, 1358-1362 ª 2018 The International Society of Dermatology While the capacity of teledermatology to improve skin healthcare and general aspects of education has been studied, it remains unclear whether it may be used to improve global health education for dermatologists and dermatology trainees.…”
Section: Introductionmentioning
confidence: 99%